Sensitized vasoactive C-nociceptors: key fibers in peripheral neuropathic pain - Forstenpointner, Julia (Pain Rep, 2019)
INTRODUCTION: Multiple mechanisms are involved in the development and persistence of neuropathic pain. Some patients with nerve damage will remain painless and develop a “loss of function” phenotype, whereas others develop painful neuropathies. OBJECTIVES: The aim of this study is to investigate the role of a peripheral nervous system sensitization by analyzing patients with and without pain. METHODS: The topical application of capsaicin was investigated in peripheral nociceptors. Two groups of patients (painful vs painless) with length-dependent neuropathies and small-fiber impairment were tested. Quantitative sensory testing was assessed before and after topical application of 0.6% capsaicin in the affected skin. In addition, blood perfusion measurements and an axon reflex flare assessment were performed. RESULTS: Quantitative testing revealed that heat hyperalgesia was induced in all patients and volunteers (P < 0.01) without observing any significant differences between patient groups. By contrast, the extent of the axon reflex flare reaction (P < 0.01) as well as the blood perfusion (P < 0.05) was significantly greater in patients with pain than in neuropathy patients not experiencing pain. CONCLUSION: Hyperexcitable vasoactive nociceptive C fibers might contribute to pain in peripheral neuropathies and therefore may serve as a key player in separating into a painless or painful condition.